(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The development of all spheres of human activity is associated with an increase in anthropogenic pressure on environment. Metropolitan areas and large cities are experiencing the greatest pressure. Both the development of new areas adjacent to built-up areas, as well as operating existing industrial and residential complexes suffer the influences. The article presents the results of a soil study conducted in the city of Novokuibyshevsk to determine the prospects for future growth of the city. Soil samples were taken throughout the city. When choosing the place of sampling, the locations of highways, industrial zones and residential buildings were taken into account. Soil testing was carried out to obtain data on the concentrations of heavy metals (lead, zinc, copper, cadmium, nickel, manganese, etc.), as well as sulfates and nitrates. The results were analyzed and contrasted with the standards and results of previous years.Based on the study of the current state of the soil, the authors assessed the degree of pollution of urban soils in an industrial city. In their study they proposed and developed measures to improve the condition of the soil, namely, analyzed the efficiency of using phytoremediation to reduce soil contamination in residential areas of the city.